Cancer incidence and mortality among temporary maintenance workers in a refinery/petrochemical complex in Korea. (April 2014) - Koh, Dong-Hee; Chung, Eun-Kyo; Jang, Jae-Kil; Lee, Hye-Eun; Ryu, Hyang-Woo; Yoo, Kye-Mook; Kim, Eun-A; Kim, Kyoo-Sang
Abstract : Background: Petrochemical plant maintenance workers are exposed to various carcinogens such as benzene and metal fumes. In Korea, maintenance operations in petrochemical plants are typically performed by temporary employees hired as contract workers. Objectives: The purpose of this retrospective study was to evaluate cancer risk in temporary maintenance workers in a refinery/petrochemical complex in Korea. Methods: Subjects consisted of 14 698 male workers registered in a regional petrochemical plant maintenance workers union during 2002–2007. Cancer mortality and incidence were identified by linking with the nationwide death and cancer registries during 2002–2007 and 2002–2005, respectively. Standardized mortality ratios (SMRs) and standardized incidence ratios (SIRs) were calculated for each cancer. Results: Increased SMR 3·61 (six cases, 95% CI: 1·32–7·87) and SIR 3·18 (five cases, 95% CI: 1·03–7·42) were observed in oral and pharyngeal cancers. Conclusion: Our findings may suggest a potential association between oral and pharyngeal cancers and temporary maintenance jobs in the petrochemical industry. Future studies should include a longer follow-up period and a quantitative exposure assessment.